Stochastic evolutionary game analysis of food cooperation among countries along the Belt and Road from the perspective of food security - Qinghua, Mao; Linyao, Xu; Qilong, Sun; Mengxin, Guo (Frontiers in Sustainable Food Systems, 2023)
Introduction In recent years, the combination of the public health crisis and the climate crisis has greatly weakened the resilience of food systems. The Belt and Road food cooperation will make outstanding contributions to consolidate food security and reduce global poverty in countries along the Belt and Road. Methods This paper constructs a three-party stochastic evolutionary game model from the perspective of food security, distinguishes the difference between large and small countries by calculating the cereal self-sufficiency rate, which studies the cooperation strategy with the Belt and Road cereal large countries, cereal small countries and regulatory committees as the object. In addition, we introduce the Gaussian white noise characteristics to characterize the stochastic disturbance of the game system. Then we combine the mathematical derivation of the stochastic evolutionary game analysis with the simulation method, examine the effect of the stochastic disturbance factors on the cooperation, and find out the factors that affect the cooperation. And finally verifies the model and proves the reasonableness and practicability of the model. Results The stochastic evolutionary game model analyzes the interaction of stochastic disturbance and influencing factors from a dynamic perspective, and the stability of evolution is related to the strength of Gaussian white noise. The level of effort of large cereal countries and the incentives of regulatory committees can have a positive impact, but high income in small cereal countries can lead to instability in the strategic choices of other players. Discussion Taking the countries along the Belt and Road as the research object, Gaussian white noise is introduced to describe the stochastic external environment, discriminate the stability of the game system through stochastic differential equations, and analyze the influencing factors of the dynamic behavioral strategies of the parties in combination with simulation methods. To improve the capacity of national food security governance and help improve the resilience of the world food system.